Oral health status of 12-year-old school children in Khartoum state, the Sudan; a school-based survey - Ali Raouf; Trovik Tordis; Nurelhuda Nazik; Ahmed Mutaz (BMC, 2009)
Abstract Background Few studies have investigated the prevalence of dental caries among school children in the past decades in Sudan rendering it difficult to understand the status and pattern of oral health. Methods A school-based survey was conducted using stratified random cluster sampling in Khartoum state, Sudan. Data was collected through interviews and clinical examination by a single examiner. DMFT was measured according to WHO criteria. Gingival index (GI) of Loe & Silness and Plaque index (PI) of Silness & Loe were used. Results The mean DMFT for 12-year-olds was found to be 0.42 with a significant caries index (SiC) of 1.4. Private school attendees had significantly higher DMFT (0.57) when compared to public school attendees (0.4). The untreated caries prevalence was 30.5%. In multivariate analysis caries experience (DMFT > 0) was found to be significantly and directly associated with socioeconomic status. The mean GI for the six index teeth was found to be 1.05 (CI 1.03 - 1.07) and the mean PI was 1.30 (CI 1.22 - 1.38). Conclusion The prevalence of caries was found to be low. The school children with the higher socioeconomic status formed the high risk group.